Ubiquitin-proteasome system participates in the de-aggregation of spermadhesins and DQH protein during boar sperm capacitation. Issue 3 (March 2019) - Zigo, Michal; Jonakova, Vera; Manaskova-Postlerova, Pavla; Kerns, Karl; Sutovsky, Peter
Abstract : We studied the participation of the ubiquitin-proteasome system (UPS) in spermadhesin release during in vitro capacitation (IVC) of domestic boar spermatozoa. At ejaculation, boar spermatozoa acquire low molecular weight (8–16 kDa) seminal plasma proteins, predominantly spermadhesins, aggregated on the sperm surface. Due to their arrangement, such aggregates are relatively inaccessible to antibody labeling. As a result of de-aggregation and release of the outer layers of spermadhesins from the sperm surface during IVC, antibody labeling becomes feasible in the capacitated spermatozoa. In vivo, the capacitation-induced shedding of spermadhesins from the sperm surface is associated with the release of spermatozoa from the oviductal sperm reservoir. We took advantage of this property to perform image-based flow cytometry to study de-aggregation and shedding of boar spermadhesins (AQN, AWN, PSP protein families) and boar DQH (BSP1) sperm surface protein which induces higher fluorescent intensity in capacitated vs ejaculated spermatozoa. Addition of a proteasomal inhibitor (100 µM MG132) during IVC significantly reduced fluorescence intensity of all studied proteins ( P < 0.05) compared to vehicle control IVC. Western blot detection of spermadhesins did not support their retention during IVC with proteasomal inhibition ( P > 0.99) but showed the accumulation of DQH ( P = 0.03) during IVC, compared to vehicle control IVC. Our results thus demonstrate that UPS participates in the de-aggregation of spermadhesins and DQH protein from the sperm surface during capacitation, with a possible involvement in sperm detachment from the oviductal sperm reservoir and/or sperm-zona pellucida interactions. The activity of sperm UPS modulates de-aggregation of boar spermadhesins and DQH sperm surface protein/binder of sperm1 (BSP1) during the sperm capacitation.